2012
DOI: 10.1016/j.jiph.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of syringes, needles, and lancets used by diabetic patients in Pakistan

Abstract: The common disposal of sharps in the household garbage has implications for disease transmission. Education on the safe disposal of sharps may improve the disposal practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 13 publications
(16 reference statements)
9
36
0
1
Order By: Relevance
“…Among the waste generated by patients with DM in their homes, the occurrence of pens and insulin vials, needles, syringes, lancets, cotton and reagent tapes was noted. It is estimated that more than 7,500,000 syringes are used in households per year, with diabetic patients being the majority of users, and this number does not include the number of lancets used by the 25 million people with DM (18)(19) . Given this, it has been suggested that syringes and disposable needles may be reused by the user of insulin, up to eight times, as long as the needle hasn't been contaminated, or caused discomfort during administration.It has also been suggested that syringes and needles may be kept at room temperature, and, after use, that the syringe should be covered, cleaning the needle with alcohol not being recommended (1) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the waste generated by patients with DM in their homes, the occurrence of pens and insulin vials, needles, syringes, lancets, cotton and reagent tapes was noted. It is estimated that more than 7,500,000 syringes are used in households per year, with diabetic patients being the majority of users, and this number does not include the number of lancets used by the 25 million people with DM (18)(19) . Given this, it has been suggested that syringes and disposable needles may be reused by the user of insulin, up to eight times, as long as the needle hasn't been contaminated, or caused discomfort during administration.It has also been suggested that syringes and needles may be kept at room temperature, and, after use, that the syringe should be covered, cleaning the needle with alcohol not being recommended (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Even when they put the waste in PET bottles, it ends up being thrown in common trash cans at the moment of disposal. They should be instructed that it is not enough to just separate the sharp materials; it is necessary to analyze the possible treatment and final destination, to minimize the impact on the environment (17)(18)(19)(20) . Few patients carried out the proper disposal of sharp materials, because many did not use appropriate containers and did not deliver the material in the health unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interviewer-administered questionnaire was used to collect information. The structured questionnaire was developed using pre-identified questions from similar international journal articles [7, 8]. The issues explored insulin administration practices, equipment used, the frequency of needle use, disposal of insulin syringes and pens, lancet disposal, sharing of needles and knowledge about disease spread by sharing needles.…”
Section: Methodsmentioning
confidence: 99%